Community participation in low-income housing projects : experiences of newly-urbanised Africans in Mfuleni in the Cape Metropole - Baba, Mbulelo Mazizi (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Public Management and Planning))--University of Stellenbosch, 1998.